When your best isn't good enough : the secret of measuring up (Grand Rapids, Mich. : Revell, 1998)
1. Self-doubt. 2. Failure (Psychology) 3. Perfectionism (Personality trait). 4. Expectation (Psychology) 5. Self-perception.
Faculty